A review on carbon nanotube field effect transistors (CNTFETs) for ultra-low power applications. (June 2018) - Prakash, P.; Mohana Sundaram, K.; Anto Bennet, M.
Abstract: Presently, the battery life and high spectral efficiency are found to be a perennial problem in smartphones. With the advancement in the technologies towards 5 G, it has become mandatory to meet these challenges before problems are aggravated. Besides, CNTFET technology is found to be a promising field of research that is recommended in this review to solve these problems. The intention of this study is to provide an overview of most recent research on the state-of-the-art of CNTFETs. Several papers were reviewed that include the device modeling, simulation, device fabrication and its applications. However, the majority of these papers were observed to deal with digital applications, while the papers related to analog applications were limited. Moreover, this review provides the information regarding the results obtained from the device circuit performance and the scope for future prospects. Highlights: CNTFETs are the most suitable alternative for the conventional CMOS. CNTFET based circuits are expected to be 3× faster than silicon transistors, while consuming the same power. CNTFET technology has a bright future in the area of Mobile and wireless RF applications.